2018
DOI: 10.1002/term.2694
|View full text |Cite
|
Sign up to set email alerts
|

A bioartificial kidney device with polarized secretion of immune modulators

Abstract: The accumulation of protein-bound toxins in dialyzed patients is strongly associated with their high morbidity and mortality. The bioartificial kidney device (BAK), containing proximal tubule epithelial cells (PTECs) seeded on functionalized synthetic hollow fibre membranes, may be a powerful solution for the active removal of those metabolites. In an earlier study, we developed an upscaled BAK containing conditionally immortalized human PTEC with functional organic cationic transporter 2. Here, we first exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Bioartificial kidneys (BAKs) (Figure 3) are membranes that mimic native kidney processes by engaging a monolayer of conditionally immortalized proximal tubule epithelial cells (ciPTECs) cultured on polymeric membranes and collagen IV [42]. Two in-vitro studies demonstrated that ciPTECs are living cells that perform their functions well: they secrete proinflammatory cytokines and organic cation transporter 2, transport ions well, and are inhibited by H2-receptor antagonists [48,49]. They have been shown to achieve the secretory clearance of human serum albumin-bound uremic toxins that cannot be removed by commercial membranes, including IS (MW: 213 Da) and kynurenic acid (MW: 189 Da), as well as of albumin (MW: 66,500 Da) [49].…”
Section: Bioartificial Kidneysmentioning
confidence: 99%
“…Bioartificial kidneys (BAKs) (Figure 3) are membranes that mimic native kidney processes by engaging a monolayer of conditionally immortalized proximal tubule epithelial cells (ciPTECs) cultured on polymeric membranes and collagen IV [42]. Two in-vitro studies demonstrated that ciPTECs are living cells that perform their functions well: they secrete proinflammatory cytokines and organic cation transporter 2, transport ions well, and are inhibited by H2-receptor antagonists [48,49]. They have been shown to achieve the secretory clearance of human serum albumin-bound uremic toxins that cannot be removed by commercial membranes, including IS (MW: 213 Da) and kynurenic acid (MW: 189 Da), as well as of albumin (MW: 66,500 Da) [49].…”
Section: Bioartificial Kidneysmentioning
confidence: 99%
“…Cultures of renal epithelial cells in hollow fiber membranes demonstrate differential transport of organic cation compounds with scaled up versions of this format intended to serve to treat patients with uremic syndrome. [73][74][75] The device demonstrates OCT2 and OAT1 transporter functions with correct cellular localization. A similar bioartificial kidney is under development at the University of Michigan to treat patients with acute kidney failure.…”
Section: Hollow-fiber Culture Techniquesmentioning
confidence: 99%
“…[20][21][22][23] Although expression of kidney-specific transporters can be observed in vitro, renal tubule cells in 2D and 3D culture lack fully elaborated brush borders and may not express a complete complement of transporters. 2,1,15 Apicobasal fluid transport independent of hydrostatic pressure gradients has to our knowledge only been observed in fresh intact tubules. 24 Multiple investigators have reported enhanced expression of various kidney-specific proteins when tubule cells are cultured in three-dimensional hydrogels.…”
Section: Proximal Tubule Cell Morphology Varies With Substrate Elasticitymentioning
confidence: 99%
“…The stiffnesses chosen are similar to those used in a number of in vitro studies in multiple cell types, including kidney epithelial cells. 14,15…”
Section: Introductionmentioning
confidence: 99%